Strategic Framework for Extended Producer Responsibility of Used Beverage Carton Packaging Using Analytical Hierarchy Process - Annisa, Siti; Mizuno, Kosuke; Sodri, Ahyahudin (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
The rapid expansion of urban populations and changing consumption behaviors have intensified solid waste challenges, particularly in developing countries like Indonesia. Used beverage cartons (UBCs), composed of layered paper, plastic, and aluminum, are among the most difficult packaging materials to recycle. Extended Producer Responsibility (EPR) is increasingly promoted as a policy mechanism to shift waste management responsibilities from local governments to producers. However, the implementation of EPR in Indonesia remains limited due to weak infrastructure, low market incentives, and fragmented stakeholder coordination. This study aims to identify strategic priorities for EPR implementation in managing UBC waste by applying the Analytical Hierarchy Process (AHP), integrated with a penta-helix stakeholder framework. Conducted in East Jakarta between March and November 2023, the research engaged five expert informants representing government, academia, industry, civil society, and waste management sectors. Through structured pairwise comparisons, the study evaluated five sub-criteria: stakeholder participation, regulatory framework, financial incentives, market access for recycled UBCs, and recycling technology. The AHP analysis revealed that stakeholder participation holds the highest priority weight (48.31%), followed by the regulatory framework (34.57%) and financial incentives (9.64%). Market and off-taker availability (5.63%) and recycling technology advancement (1.85%) were identified as lower-priority but still necessary components. These results indicate that socio-economic considerations dominate strategic decision-making in UBC waste management. The study offers a data-driven and context-sensitive framework for EPR implementation that can inform policymakers and industry actors. Furthermore, the AHP model demonstrates potential for replicability in other complex waste streams requiring coordinated multi-stakeholder engagement.